Estudio de prefactibilidad para la instalación de un servicio de alquiler de vehículos - Paredes Palomino, Jorge Armando (2019)
The present project consists in a pre-feasibility study for the implementation of a car rental service in the city of Lima Metropolitana and to be implemented in the northwest zone of the Surquillo’s district. The principal revenues that the project will get will come from the car rental for enterprises, for businessmen and or foreigners investors, tourists, natural persons and or for those who have taken their car for maintenance in the brand’s house. It is planned that the demand mentioned, according to the calculations made during the investigation, and based on statistic data, be of 13 572 rental days for the first year and of 16 090 rental days for the fifth year of running the project; which means that there must be an approximate fleet of 41 vehicles for the first year and 48 vehicles for the fifth year. Based on the demand calculated, it is estimated that the investment required for running up the project is of 4 230 608 soles, which include the acquisition of the initial fleet of vehicles (41), the ground, the infrastructure, furniture and the smart parking; as well as working capital required for starting the project. In order to be able to finance the aforementioned investment, a request for a loan equivalent to 60% of the total amount will be requested. According to the analysis made in the research, economically and financially, the project results factible, because it possesses, according to the economic evaluation, an economic VAN of 729 630 soles, an economic TIR of 23,20% (with a weighted average cost of capital (CPPC) of 11,76%), a R (B/C) ratio of 1,17 and a recovery period of 4,09 years. Likewise, in the results of the financial evaluation, it was obtained a financial VAN of 1 289 283 soles, a financial TIR of 33,31%, a R (B/C) ratio of 1,76 and a recovery period of 4,13 years. In addition, the analysis of the above results shows very favorable liquidity, solvency, profitability and social impact indicators. Finally, based on the above, it is determined that the project is technically, economically, financially and socially factible. In this way, the hypothesis proposed at the beginning of the investigation results to be true.